2010
DOI: 10.1016/j.labeco.2010.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Over-education for the rich, under-education for the poor: A search-theoretic microfoundation

Abstract: This paper studies the efficiency of educational choices in a two sector/two schooling level matching model of the labour market where a continuum of heterogenous workers allocates itself between sectors depending on their decision to invest in education. Individuals differ in ability and schooling cost, the search market is segmented by education, and there is free entry of new firms in each sector. Self-selection in education originates composition effects in the distribution of skills across sectors. This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…19 See Becker (1962) for more on this subject. 20 See also Charlot and Decreuse (2005), Charlot and Decreuse (2010) and references therein on the impact of the composition effect on the incentives to become educated. Rosenzweig and Evenson (1977) and Rosenzweig (1990) stated that low schooling enrollment in developing economies is the result of high schooling costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 See Becker (1962) for more on this subject. 20 See also Charlot and Decreuse (2005), Charlot and Decreuse (2010) and references therein on the impact of the composition effect on the incentives to become educated. Rosenzweig and Evenson (1977) and Rosenzweig (1990) stated that low schooling enrollment in developing economies is the result of high schooling costs.…”
Section: Discussionmentioning
confidence: 99%
“…The present model is related to the growing literature on school quality and returns to schooling investments by Jensen (), Eide and Showalter (), Sauer and Zagler (), Hanushek (), and Card and Krueger (). However, the most closely related literature is that of Charlot and Decreuse (, ). All models consider the problem of self‐selection in education in a friction environment.…”
Section: Introductionmentioning
confidence: 99%
“…The private return to education therefore exceeds the social one, and the optimal policy is to set a tax on education. In addition, Charlot and Decreuse (2010) found that the optimal education policy is to set a tax on education to deter too low ability agents from schooling.…”
Section: Discussionmentioning
confidence: 99%
“…As the latter effect reflects a private and not social gain, workers may over-invest in their education (Charlot and Decreuse, 2005). Third, and in a mechanism highlighted by Charlot and Decreuse (2010), the presence of heterogeneity in worker ability also generates an externality. As the average ability level within education increases, there is an increase in the intensity of job creation for the associated skill requirement.…”
Section: The Joint Distribution Of Matches Is Stationarymentioning
confidence: 99%